Climate Change Adaptation in Batang Hari, Jambi: A Case Study of Rainfed Paddy Farmers - Nasution, Mulia; Purnama, Setyawan; Sekaranom, Andung Bayu (Faculty of Geography, Universitas Gadjah Mada, 2024)
Batang Hari is situated as one of the central rice-producing regencies within Jambi Province. However, the agricultural sector in Batang Hari is severely impacted by climate change in the context of productivity. This study aimed to examine rainfall and temperature trends over the last 20 years (2002 to 2021), assess farmers' perceptions, and identify the current adaptation measures due to the impact of climate change on rainfed paddy fields. This study is of great importance because it employs a holistic approach, integrating quantitative data on climate trends with qualitative insights from farmers. The results showed that rainfall decreased by 20–50 mm/month, and the average temperature increased by 0.4°C in 20 years. The qualitative data on farmers' perceived impact of changes in climate variability reported an agreement with climatological data. The farmers perceived a decrease in rainfall and a concurrent rise in temperatures. Furthermore, a delayed onset of the rainy season was noted, leading to an adjustment of their planting schedules. Certain adaptation measures to adjust to the perceived impact of changes in climate variability on their rainfed paddy fields were also implemented. These measures included crop management as well as socio-economic adaptation. Farmers' adaptation measures included modifying crop varieties, adjusting planting seasons, adopting agricultural machinery, and diversifying income through off-farm activities. It is also important to emphasize technological based adaptation to enhance climate resilience, as well as sustainable land management practices, agroforestry initiatives, and soil conservation efforts for long-term agricultural sustainability.